2022
DOI: 10.1039/d2qo00966h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic differences between aryl iodide electrophiles and pronucleophiles in Pd-catalyzed coupling with cyclopropenes: a DFT study

Abstract: Computational studies were carried out to investigate the mechanisms of Pd-catalyzed ring-opening reactions of cyclopropenes with pronucleophiles (H-Nu) and aryl iodide electrophiles, respectively. The mechanistic path for the reaction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Here, the internal base of the Pd( ii ) salt apparently affected the olefination rate, and a strong internal base offered a relatively faster olefination rate, indicating that it was a base-assisted β-hydride elimination process. 50–52 However, in the 1 H NMR kinetics study of the olefination reaction, no reactive intermediate was observed prior to the olefination product formation (Fig. S21†), even when Pd(TFA) 2 was employed as the Pd( ii ) source, implying that the whole olefination reaction was still a fast process in the C–H activation and functionalization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the internal base of the Pd( ii ) salt apparently affected the olefination rate, and a strong internal base offered a relatively faster olefination rate, indicating that it was a base-assisted β-hydride elimination process. 50–52 However, in the 1 H NMR kinetics study of the olefination reaction, no reactive intermediate was observed prior to the olefination product formation (Fig. S21†), even when Pd(TFA) 2 was employed as the Pd( ii ) source, implying that the whole olefination reaction was still a fast process in the C–H activation and functionalization reaction.…”
Section: Resultsmentioning
confidence: 99%